Emerging paper microfluidic devices. Issue 22 (7th October 2019) - Gao, Bingbing; Li, Xin; Yang, Yaqiong; Chu, Jianlin; He, Bingfang
Abstract : Paper has unique advantages over other materials, including low cost, flexibility, porosity, and self-driven liquid pumping, thus making it widely used in various fields in biology, chemistry, physics and materials science. Abstract : Paper has unique advantages over other materials, including low cost, flexibility, porosity, and self-driven liquid pumping, thus making it widely used in various fields in biology, chemistry, physics and materials science. Recently, many multifunctional and highly integrated membrane-based devices have been achieved with the rapid development of membrane-building materials such as paper and pseudo-paper. Therefore, the rigid boundary between paper and other membranes has become blurred; paper can be considered a flexible membrane, and membranes with appropriately flexible or porous structures can also be defined as paper. Paper can manipulate liquids and respond photoelectrically to external objects to be measured, making it suitable for (bio)chemical sensing (chromatographic analysis, electrochemical analysis and wearable sensing). This review focuses on the development of microfluidic devices built with both traditional paper and other flexible membranes, including fabrication, (bio)chemical sensing, microfluidics manipulation and multiple applications.